Respuesta :

Answer:

Step-by-step explanation:

Let's retype that as y = b^x.  The inverse of this function is log    y = x  

                                                                                                        b

which you could also write as  y = ln     x

                                                             b

If you had y = e^x, the inverse function would be y = ln x.

Note that if you let ln x be the input to y = e^x, the result would be just 'x,' which confirms that these two functions are inverses of one another.